Scientific research project: Biomechanical analyses at the 12th IAAF World Championships in athletics 2009. Final report. Combined events. (DLV, 2009)
Final report of the biomechanical analyses of the combined events at the 12th IAAF World Championships in athletics, Berlin 12.-23. August 2009 within the frame of a project of the German Athletics Federation (DLV) in co-operation with the Institute of Applied Training Science Leipzig, the Olympic Training Bases Berlin, Hesse and Rhineland and the Martin-Luther-University Halle/Wittenberg.